Factors Predicting Functional Ability among Older Adults undergoing Hip and Knee Arthroplasty - aree-ue, suparb; Roopsawang, Inthira; Kawinwonggowit, Viroj (Pacific Rim International Journal of Nursing Research, 2019)
Total joint arthroplasty is a standard surgical procedure for reducing chronic joint pain and improving functions along with quality of life among older adults with osteoarthritis. Preoperative patients’ expectation to improve health outcomes and quality of care transitions are imperative concerns involving postoperative patient recovery. This prospective correlational study aims were to describe the patients’ expectation to improve functional ability, quality of care transition, and health outcomes (functional ability) among older adults undergoing hip and knee arthroplasty and to investigate the predictive power of patients’ expectation along with quality of care transition to functional ability at two week follow-ups after total joint arthroplasty. Ninety-five participants scheduled for total hip and knee arthroplasty completed questionnaires, which included the Demographic and Health Information Questions, Patients’ Expectation Questionnaire, Care Transition Measure-15, and Modified Barthel Activities of Daily Index. Data were analyzed by using descriptive statistics, Pearson’s coefficient correlation, and backward regression analysis. Results showed that the participants had a moderate level of patients’ expectation and quality of care transition, whereas a high level of functional ability was discovered. Patients’ expectation and quality of care transition were positively related to functional ability. The walking ability and social participation subscales of patients’ expectation along with management preparation and critical understanding components of quality of care transition were the predictors of functional ability. These variables were jointly predicted functional ability. A better understanding of the association among patients’ expectation, quality of care transition, and functional ability may improve the process of care and clinical outcomes among older adults undergoing hip and knee arthroplasty.